Blue exorcist. 03 - Kato, Kazue, 1980- (Shonen Jump advanced., 2011)
As a new Exorcist esquire at True Cross Academy. Rin Okumura has a long way to go before he reaches the top rank of Paladin. When Rin and his classmates are sent to search for a ghost. Amaimon, King of Earth, takes Rin by surprise and steals the Koma sword, Higher powers have been observing events at the Academy and make their presence known. New players enter the game, and Rin doesn't even know he's playing.